Application of the Gamification Model in Islamic Religious Education Learning to Increase Student Learning Motivation in Vocational High Schools - ati, Sumi; RN, Bustanul Iman; Pamessangi, Andi Arif; Astuti, Sindi (South Sulawesi Education Development (SSED), 2025)
This study explores the application of a gamification model in Islamic Religious Education to enhance student learning motivation. The research aims to examine the implementation of gamification in the learning process and its impact on the motivation of class XI TKR A students. Using Classroom Action Research, the study involved 21 students and collected data through observation, questionnaires, and documentation. Data analysis included evaluating teacher and student activity sheets and motivation questionnaires. Results show that teacher activity improved from 63% in cycle I to 90.8% in cycle II, student activity increased from 54% to 91%, and student motivation rose from 62% to 86%. These findings indicate that gamification significantly enhances student engagement and motivation in Islamic Religious Education learning.